Targeting MAPK Pathways by Naringenin Modulates Microglia M1/M2 Polarization in Lipopolysaccharide-Stimulated Cultures - Zhang, Bei; Wei, Yi-Zheng; Wang, Guo-Qing; Li, Dai-Di; Shi, Jing-Shan; Zhang, Feng (Frontiers in Cellular Neuroscience, 2019)
Neuroinflammation is considered to be an important and inevitable pathological process associated with all types of damages to, and disorders of, the central nervous system. The hallmark of neuroinflammation is the microglia activation. In response to different micro-environmental disturbances, microglia could polarize into either an M1 pro-inflammatory phenotype, exacerbating neurotoxicity, or an M2 anti-inflammatory phenotype, exerting neuroprotection. Therefore, shifting the polarization of microglia toward the M2 phenotype could possess a more viable strategy for the neuroinflammatory disorders treatment. Naringenin (NAR) is naturally a grapefruit flavonoid and possesses various kinds of pharmacological activities, such as anti-inflammatory and neuroprotective activities. In the present study, we aimed to investigate the potential effects of NAR on microglial M1/M2 polarization and further reveal the underlying mechanisms of actions. First, NAR inhibited lipopolysaccharide (LPS)-induced microglial activation. Then, NAR shifted the M1 pro-inflammatory microglia phenotype to the M2 anti-inflammatory M2 microglia state as demonstrated by the decreased expression of M1 markers (i.e., inducible TNF-α and IL-1β) and the elevated expression of M2 markers (i.e., arginase 1, IL-4 and IL-10). In addition, the effects of NAR on microglial polarization were dependent on MAPK signaling, particularly JNK inactivation, as evidenced by the fact that the selective activator of JNK abolished NAR-promoted M2 polarization and further NAR-inhibited microglial activation. Together, this study demonstrated that NAR promoted microglia M1/M2 polarization, thus conferring anti-neuroinflammatory effects via the inhibition of MAPK signaling activation. These findings might provide new alternative avenues for neuroinflammation-related disorders treatment.